PENGARUH FLOW EXPERIENCE, PERCEIVED ENJOYMENT, PERFORMANCE EXPECTANCY, EFFORT EXPECTANCY, SOCIAL INFLUENCE, DAN FACILITATING CONDITIONS TERHADAP BEHAVIORAL INTENTION PEMAIN MOBILE GAME KOTA KITA - Bongso, Reky Wiryanto; Dewi, Citra Kusuma (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2021)
The study aims to construct findings of impact between the flow experience, perceived enjoyment, performance expectancy, effort expectancy, social influence, and facilitating conditions toward the behavioral intention of Kota Kita mobile game players. For this study we applies a quantitative research methodology with non-probability sampling techniques. Using number of samples as many as 100 people of Kota Kita mobile game players in Indonesia. This study also employs descriptive analysis techniques and multiple linear regression for analysis purpose.The partial hypothesis test results show there is no significant effect between flow experience, performance expectancy, and effort expectancy on behavioral intention. Meanwhile, there is a significant effect between perceived enjoyment, social influence, and facilitating conditions toward behavioral intention on Kota Kita players. Furthermore, based on the results of the f test show that simultaneously, there is an effect between flow experience, perceived enjoyment, performance expectancy, effort expectancy, social influence, and facilitating conditions toward behavioral intention on Kota Kita players.